MathQuest: A powerpoint-based problem-based learning game for mathematical problem-solving - Reny Supartini; Nenden Mutiara Sari; In In Supianti; Gina Dwi Septiani (CV. FOUNDAE, 2024)
Background: Despite the importance of mathematical problem-solving skills in academic and everyday contexts, many students struggle to master these skills due to the lack of engaging and effective instructional tools. Traditional teaching methods often fail to address these challenges, highlighting the need for innovative approaches that integrate interactive and motivating elements into the learning process.Aims: This study aims to develop and validate a PowerPoint-based Problem-Based Learning (PBL) game, evaluate its practicality in classrooms, and assess its effectiveness in improving students' mathematical problem-solving skills and motivation.Methods: Using the ADDIE model, this research involved 33 tenth-grade students selected through purposive sampling. Validation by two media experts, two content experts, and two language experts ensured high-quality game design.Result: Expert validation results showed high scores for content (91 percent), media design (89 percent), and language clarity (92 percent), indicating strong validity. The game achieved a practicality score of 85 percent based on student usability feedback. Effectiveness was demonstrated through a significant improvement in students’ mathematical problem-solving skills, with average test scores increasing from 65 to 85 after using the game. Additionally, 70 percent of students reported heightened motivation and engagement in learning mathematics through this game.Conclusion: The PBL-based PowerPoint game demonstrated strong validity, practicality, and effectiveness in addressing the needs of students and enhancing their mathematical skills. Key educational game elements identified include immediate feedback, question variety, and the ability to play in groups, making it a viable tool for classroom implementation.